Analisis Daya Dukung Pondasi Jembatan (Studi Kasus : Jembatan W6 Kota Pagar Alam) - M.Sang Gumilar; Arman Sulistio (JURNAL ILMIAH BERING'S, 2018)
The bridge is a construction built to correlate the roads broken off by the existence of a river or strait. In this bridge foundation research aims to see the stability of the foundation on the carrying capacity of the soil, the ultimate carrying capacity (qult), stability of shear, rolling and slope. From the results of the study the bridge obtained a total weight of 10633,017 Ton / m 'of bearing capacity, 260,613 kg / m², ultimate carrying capacity (qult), 656.85 kg / m², stability against shear 4.76> 1.5 safe against shear force soil, rolling factor with a value of 7.70 > 1.5 safe against rolling force, bearing capacity of 2, 52 > 2.5 safe for landslides.